2012
DOI: 10.1155/2012/152747
|View full text |Cite
|
Sign up to set email alerts
|

Students' Persistence and Academic Success in a First-Year Professional Bachelor Program: The Influence of Students' Learning Strategies and Academic Motivation

Abstract: The present study explores whether students' learning strategies and academic motivation predict persistence and academic success in the first year of higher education. Freshmen students in a professional bachelor program in teacher education were questioned on their learning strategy use and motivation at the start and at the end of the academic year. Students' learning strategies were assessed using the inventory of learning styles-SV. Motivation was measured using scales from the self-regulation questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 45 publications
3
43
0
9
Order By: Relevance
“…In contrast, those who are extrinsically motivated usually have lower levels of SE (Friedal et al, 2007), with studies reporting mixed findings regarding the relationship between academic achievement, SE, and extrinsic motivation (Bong, 2005;Harackiewicz, Barron, Tauer, Carter, & Elliot, 2000). High amotivation has also been associated with lower SE (Turner, Chandler, & Heffer, 2009), poorer academic success (Vanthournout, Gijbels, Coertjens, Donche, & Van Petegem, 2012), and feeling that a behaviour is beyond one's control (Legault et al, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, those who are extrinsically motivated usually have lower levels of SE (Friedal et al, 2007), with studies reporting mixed findings regarding the relationship between academic achievement, SE, and extrinsic motivation (Bong, 2005;Harackiewicz, Barron, Tauer, Carter, & Elliot, 2000). High amotivation has also been associated with lower SE (Turner, Chandler, & Heffer, 2009), poorer academic success (Vanthournout, Gijbels, Coertjens, Donche, & Van Petegem, 2012), and feeling that a behaviour is beyond one's control (Legault et al, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although initially MOOCs students are highly motivated, only a very small number persist until the end of the course (e.g., Clow, 2013;MOOCs@Edinburgh Group, 2013). Previous studies show that lack of persistence in online environments is associated with low levels of motivation (Hart, 2012;Vallerand, Fortier, & Guay, 1997;Vanthournout, Gijbels, Coertjens, Donche, & Van Petegem, 2012). However, not much is known about how this relationship functions in an environment where students are initially highly motivated, such as MOOCs.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the meaning-directed learning style had a low positive association with academic performance, whereas the undirected learning style had a low negative association with academic performance (Boyle, Duffy, & Dunleavy, 2003). Other studies, for example Vanthournout et al (2012) and Komarraju et al (2012) have suggested that learning styles may influence academic performance. This research attempts to determine the extent to which learning styles influence academic performance in the current setup.…”
Section: Learning Styles and Academic Performancementioning
confidence: 86%